Democracias coroadas?: o impacto da forma monárquica de governo nas democracias contemporâneas - Nicastro, Guilherme de Faria (2026)
The study analyzes the role of the monarchical form of government in contemporary liberal democracies, investigating whether the maintenance of a hereditary and neutral head of state in parliamentary constitutional monarchies affects the development, stability, or resilience of the democratic political regime. Building on a gap identified in the legal and constitutional political literature, the study adopts the method of comparative constitutional law and a multiple–case study approach, examining the legal systems and institutional practices of the Kingdom of Belgium, the Kingdom of Spain, the United Kingdom, and the Kingdom of Sweden. The research combines historical, institutional, and empirical analysis, assessing the constitutional and political prerogatives of monarchs and confronting them with data drawn from the main international democracy assessment indices, such as the Economist Intelligence Unit’s Democracy Index, Freedom in the World, and the Varieties of Democracy (V-Dem) project. It is argued that, although Monarchy is often perceived as an anachronistic or antidemocratic institution, its institutional design — marked by the separation between the head of state and the head of government and by the neutrality of the monarch — may contribute to the moderation and mediation of state powers, political integration, and the preservation of democratic stability, especially in contexts of democratic crisis and erosion, despite the fact that international democracy assessment indices are unable to capture whether the Crowns exert a positive or negative effect on the democratic performance of the states analyzed